What is the Impact of International Remittances on Poverty and Inequality in Latin America? - Acosta, Pablo (World Bank, Washington, DC, 2012)
Workers' remittances have become a major source of income for developing countries. However, little is still known about their impact on poverty and inequality. Using a large cross-country panel dataset, the authors find that remittances in Latin American and Caribbean (LAC) countries have increased growth and reduced inequality and poverty. These results are robust to the use of different instruments that attempt to correct for the potential endogeneity of remittances. Household survey-based estimates for 10 LAC countries confirm that remittances have negative albeit relatively small inequality and poverty-reducing effects, even after imputations for the potential home earnings of migrants.